Taxonomic And Biological Studies Of Cyprinid Genus Poropuntius In Peninsular Malaysia - Abdullah Halim, Muhammad Rasul (2022)
The cyprinid fishes of the genus Poropuntius consisted of small to medium size, range 10 to 20 cm of standard length as adults are widely distributed mainly in the mainland of Southeast Asia and inhabit foothill streams at moderate elevations. Due to the confusing taxonomic, several species names have been used in the old literature in Peninsular Malaysia, namely, Poropuntius deauratus, Poropuntius normani, and Poropuntius smedleyi. This study aims to determine the taxonomical status, distributional pattern, and some biological aspects of the reproductive pattern of Poropuntius in Peninsular Malaysia. Morphology studies of 281 specimens from different localities indicated three types of Poropuntius species found in Peninsular Malaysia: Poropuntius smedleyi, Poropuntius cf. normani, and Poropuntius normani.